2016
DOI: 10.1177/0300060516662402
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between bone mineral density and dietary intake of β-carotene, vitamin C, zinc and vegetables in postmenopausal Korean women: a cross-sectional study

Abstract: ObjectiveTo examine the relationship between nutritional intake and bone mineral density (BMD) in postmenopausal Korean women.MethodsDietary intake was recorded in postmenopausal Korean women using a semiquantitative questionnaire. The frequency of consumption of various food groups and nutrient intake were calculated. BMD T-scores were measured at the lumbar spine, femoral neck and total hip using dual-energy X-ray absorptiometry. Associations between T-scores and dietary intake were analysed using partial co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
46
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(48 citation statements)
references
References 33 publications
2
46
0
Order By: Relevance
“…Previous studies on the relationship between β-carotene intake and fracture risk reported controversial results. Several population-based studies demonstrated protective effect of β-carotene on bone [ 52 , 53 ]. However, Wolf et al [ 54 ] and Melhus et al [ 55 ] have shown a negative influence of β-carotene on bone.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies on the relationship between β-carotene intake and fracture risk reported controversial results. Several population-based studies demonstrated protective effect of β-carotene on bone [ 52 , 53 ]. However, Wolf et al [ 54 ] and Melhus et al [ 55 ] have shown a negative influence of β-carotene on bone.…”
Section: Discussionmentioning
confidence: 99%
“…Out of twentyfour studies that were included in the systematic review, we excluded twenty studies because of the following reasons: those that reported results as beta regression (20) Cohort coefficient (24,25,(27)(28)(29)31,38,42,50,51,54,58,59,61) ; those that reported BMD's means and standard deviations in categories of vitamin C intake (55) or users vitamin C supplement v. non-users (52) ; those that reported relative risks (RR) and 95 % CI in tertiles of vitamin C intake (57) ; and those that measured BMD at calcaneus (56) , total forearm, trabecular forearm, cortical forearm (53) and whole body (30) . Finally, four studies (23,26,34,60) that examined the correlation between dietary vitamin C intake and BMD at femoral neck (four effect sizes obtained from four studies) and lumbar spine (three effect sizes obtained from three studies) were included in the meta-analysis. Studies that reported correlation coefficient between dietary vitamin C intake and BMD included 3529 individuals in total.…”
Section: Findings Of the Meta-analysismentioning
confidence: 99%
“…Previous human studies on the association between carotenoid intake and bone health have been performed in Western countries, including America [ 21 ], Australia [ 27 ], and Japan [ 28 ]. To the best of our knowledge, only one study has examined the association between dietary carotenoid intake and bone health in Korea [ 29 ]. That study reported a positive association between β-carotene intake and BMD in Korean postmenopausal women aged 50–75 years [ 29 ].…”
Section: Introductionmentioning
confidence: 99%
“…To the best of our knowledge, only one study has examined the association between dietary carotenoid intake and bone health in Korea [ 29 ]. That study reported a positive association between β-carotene intake and BMD in Korean postmenopausal women aged 50–75 years [ 29 ]. However, that study was conducted with a small sample size ( n = 189) and a convenience sampling method.…”
Section: Introductionmentioning
confidence: 99%